Moisture-curable polyurethane hot-melt resin composition, adhesive, and synthetic leather
By using a hot melt urethane prepolymer containing isocyanate group and a wet-curing polyurethane hot melt resin composition of a compound having a sulfonic acid group, the problems of high drying energy of the adhesive and low wettability of the PVC skin material in the prior art are solved, and excellent adhesiveness, low temperature bending and durability are achieved.
Patent Information
- Application Number
- CN202380064236.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-01
- Filing Date
- 2023-06-29
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, the water-based and solvent-free adhesives have high energy in the drying process, low production efficiency, and low wettability to adhered materials such as PVC skin materials, making it difficult to fully exert adhesive properties.
A wet cured polyurethane hot melt resin composition containing a hot melt urethane prepolymer (A) having an isocyanate group and a compound (B) having a sulfonic acid group is used to form excellent adhesion, low temperature bending and durability through specific ratios of polyol (a) and polyisocyanate (b) and reaction conditions.
Excellent adhesion, low-temperature bending and durability to materials such as polyvinyl chloride are achieved, which improves production efficiency and reduces the impact on the environment.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a moisture-curable polyurethane hot-melt resin composition, an adhesive and synthetic leather. Background Art
[0002] In synthetic leather, polyurethane (PU), polyvinyl chloride (PVC), olefin-based thermoplastic elastomer (TPO), etc. are used as surface materials, and materials obtained by bonding these surface materials to base fabrics such as cloth and non-woven fabrics with adhesives are generally used (for example, see Patent Document 1). Among them, solvent-based adhesives have been widely used and generally used so far, but as a measure for the environment, regions, countries, and companies require the reduction of VOCs, and there is a need to replace solvent-based adhesives with water-based and solvent-free adhesives.
[0003] For the water system, which is one of the VOC reduction systems, a low-viscosity compounding liquid is applied to the epidermis layer and then dried to remove the solvent, and matured if necessary to obtain a firm film. It is characterized in that due to the low viscosity, the wettability to the epidermis material is also good, and it is easy to obtain close adhesion. However, for the drying process, the drying energy increases compared to the solvent system, so production efficiency becomes a problem. On the other hand, regarding the solvent-free system, which is another VOC reduction system, polyurethane-based reactive hot melt adhesives (RHM) have been actively studied, but in the coating substrate, for adherends such as PVC epidermis materials, the wettability with RHM is generally low, and even if the previous RHM is used, it is difficult to fully exert its performance in terms of adhesion.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application No. 2008-514403 Summary of the invention
[0007] Problems to be solved by the invention
[0008] The problem to be solved by the present invention is to provide a moisture-curable polyurethane hot-melt resin composition having excellent adhesiveness, low-temperature flexibility and durability.
[0009] Means for solving problems
[0010] The present invention provides the following moisture-curable polyurethane hot-melt resin composition, characterized in that it contains a hot-melt urethane prepolymer (A) having an isocyanate group and a compound (B) having a sulfonic acid group, wherein the hot-melt prepolymer (A) uses a polyol (a) containing 50% by mass or more of a polyether polyol (a1) as a raw material, and the content of the compound (B) is in the range of 0.01 to 1 part by mass relative to 100 parts by mass of the hot-melt urethane prepolymer (A).
[0011] The present invention also provides the following adhesive, characterized in that it contains the above-mentioned moisture-curable polyurethane hot-melt resin composition. The present invention also provides the following synthetic leather, characterized in that it has at least a thermoplastic resin layer and the above-mentioned adhesive layer.
[0012] Effects of the Invention
[0013] The moisture-curable polyurethane hot-melt resin composition of the present invention has excellent adhesion (especially adhesion to polyvinyl chloride), low-temperature flexibility and durability. Therefore, the moisture-curable polyurethane hot-melt resin composition of the present invention can be particularly suitably used in the production of synthetic leather using a thermoplastic resin as a surface material. DETAILED DESCRIPTION
[0014] The moisture-curable polyurethane hot-melt resin composition of the present invention contains a hot-melt urethane prepolymer (A) having an isocyanate group made from a specific polyol (a) as a raw material and a specific amount of a specific compound (B).
[0015] In order to obtain excellent low-temperature bendability, the hot-melt urethane prepolymer (A) having an isocyanate group must be made of a polyol (a) containing 50% by mass or more of a polyether polyol (a1) as a raw material. By designing in this way, the glass transition temperature of the adhesive can be lowered, thereby obtaining excellent low-temperature bendability. The amount of the polyether polyol (a1) used is preferably 50 to 90% by mass, and more preferably 55 to 70% by mass in the polyol (a), in order to obtain better low-temperature bendability.
[0016] As the above-mentioned polyether polyol (a1), for example, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyoxyethylene polyoxypropylene glycol, polyoxyethylene polyoxytetramethylene glycol, polyoxypropylene polyoxytetramethylene glycol, etc. can be used. These polyols can be used alone or in combination of two or more. Among these, polypropylene glycol and / or polytetramethylene glycol are preferred from the aspect of obtaining more excellent low-temperature flexibility, and polytetramethylene glycol is more preferred from the aspect of obtaining further excellent heat resistance and wet heat resistance. It should be noted that as the above-mentioned polyether polyol, polyether polyols derived from plants can be used. As the above-mentioned polyether polyol derived from plants, for example, "Bio PTMG" manufactured by Mitsubishi Chemical Co., Ltd., "Bio PTG" manufactured by Hodogaya Chemical Co., Ltd., and biomass polypropylene glycol manufactured by VithalCastor Polyols can be obtained in the form of commercial products.
[0017] As the above-mentioned polyol (a), in addition to the above-mentioned polyether polyol (a), other polyols may also be used in combination. As the above-mentioned other polyols, for example, commercially available polyols such as polyester polyols, polycarbonate polyols, polybutadiene polyols, silicon diols, and acrylic diols may be used. These polyols may be used alone or in combination of two or more, and may be derived from petroleum or plants. With respect to the above-mentioned other polyols, polyester polyols are preferred from the aspect of obtaining more excellent adhesion.
[0018] The number average molecular weight of the polyol (a) is preferably 200 to 10,000, more preferably 500 to 6,000, from the viewpoint of obtaining more excellent adhesion, low temperature flexural properties, durability, and mechanical strength. The number average molecular weight of the polyol (a) is a value measured by gel permeation chromatography (GPC).
[0019] As the hot-melt urethane prepolymer (A) having an isocyanate group, for example, a reaction product of the polyol (a) and the polyisocyanate (b) can be used.
[0020] As the above-mentioned polyisocyanate (b), for example, aromatic polyisocyanates such as polymethylene polyphenyl polyisocyanate, diphenylmethane diisocyanate, carbodiimide-modified diphenylmethane diisocyanate, phenylene diisocyanate, toluene diisocyanate, and naphthalene diisocyanate can be used; aliphatic or alicyclic polyisocyanates such as hexamethylene diisocyanate, lysine diisocyanate, cyclohexane diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, xylylene diisocyanate, and tetramethylxylylene diisocyanate can be used. These polyisocyanates can be used alone or in combination of two or more, and can be derived from petroleum or plants. Among these, aromatic polyisocyanates are preferred, and diphenylmethane diisocyanate is more preferred, from the perspective of obtaining better reactivity and adhesion.
[0021] The hot-melt urethane prepolymer (A) has isocyanate groups at the polymer terminals and in the molecule. The isocyanate groups can react with moisture in the air, the substrate coated with the urethane prepolymer, or the adherend to form a crosslinked structure.
[0022] The hot-melt urethane prepolymer (A) can be produced, for example, by adding the polyol (a) dropwise to a reaction vessel containing the polyisocyanate (b), followed by heating, and reacting under conditions in which the isocyanate group of the polyisocyanate (b) is in excess relative to the hydroxyl group of the polyol (a).
[0023] The molar ratio [NCO / OH] of the hydroxyl group of the polyol (a) to the isocyanate group of the polyisocyanate (b) when the polyol (a) and the polyisocyanate (b) are reacted is preferably 1.3 to 2.5, more preferably 1.5 to 2.0, from the viewpoint of obtaining better hot melt properties, adhesiveness, durability and low-temperature flexural properties.
[0024] The isocyanate group content (hereinafter referred to as "NCO%") of the hot-melt urethane prepolymer (A) is preferably 1.2 to 5.0% by mass, and more preferably 1.7 to 3.5% by mass, from the viewpoint of obtaining more excellent hot melt property, adhesiveness, durability, and low-temperature flexural property. It should be noted that the NCO% of the hot-melt urethane prepolymer (A) is a value measured by potentiometric titration in accordance with JIS K1603-1:2007.
[0025] The compound (B) having a sulfonic acid group is an essential component in order to obtain excellent adhesion, and its content must be in the range of 0.01 to 1 part by mass relative to 100 parts by mass of the hot-melt urethane prepolymer (A) in order to achieve both excellent adhesion and durability. The content of the compound (B) is preferably 0.05 to 0.6 parts by mass relative to 100 parts by mass of the hot-melt urethane prepolymer (A) in order to maintain high levels of adhesion and durability.
[0026] As the compound (B), for example, methanesulfonic acid, ethanesulfonic acid, methanedisulfonic acid, 2-hydroxy-1-ethanesulfonic acid, sulfoacetic acid, 2-amino-1-ethanesulfonic acid, trifluoromethanesulfonic acid, benzenesulfonic acid, toluenesulfonic acid, xylenesulfonic acid, alkylbenzenesulfonic acid, etc. can be used. These compounds can be used alone or in combination of two or more. Among these, methanesulfonic acid is particularly preferred from the perspective of further improving the adhesion to polyvinyl chloride.
[0027] The moisture-curable polyurethane hot-melt resin composition of the present invention contains the hot-melt urethane prepolymer (A) and the compound (B) as essential components, but may contain other additives as necessary.
[0028] As above-mentioned other additives, for example, urethanization catalyst, neutralizing agent, crosslinking agent, silane coupling agent, thickener, filler, thixotropy imparting agent, tackifier, wax, heat stabilizer, light stabilizer, fluorescent whitening agent, foaming agent, pigment, dye, conductivity imparting agent, antistatic agent, moisture permeability improving agent, water repellent, oil repellent, hollow foam, water absorbent, moisture absorbent, deodorant, foam regulating agent, plasticizer, anti-blocking agent, hydrolysis preventing agent etc. can be used.These additives can be used alone, and two or more can be used in combination.
[0029] As described above, the moisture-curable polyurethane hot-melt resin composition of the present invention has excellent adhesiveness, low-temperature flexural properties, and durability. Therefore, the moisture-curable polyurethane hot-melt resin composition of the present invention can be particularly suitably used in the production of synthetic leather using a thermoplastic resin as a surface material.
[0030] Next, the synthetic leather of the present invention will be described.
[0031] The synthetic leather comprises at least a thermoplastic resin layer and an adhesive layer containing the moisture-curable polyurethane hot-melt resin composition, and examples thereof include synthetic leathers in which a substrate, the adhesive layer and the thermoplastic resin layer are sequentially laminated.
[0032] As the above-mentioned substrate, for example, non-woven fabrics, woven fabrics, knitted fabrics, etc. formed by polyester fibers, polyethylene fibers, nylon fibers, acrylic fibers, polyurethane fibers, acetate fibers, rayon fibers, polylactic acid fibers, cotton, linen, silk, wool, glass fibers, carbon fibers, and blended fibers thereof can be used.
[0033] As the thermoplastic resin layer, for example, a resin layer formed of known polyvinyl chloride, polyvinyl acetate, polyvinylidene chloride, polystyrene, TPO (Thermoplastic Olefinic Elastomer), thermoplastic ester elastomer, thermoplastic polyurethane, etc. can be used. In the present invention, even when polyvinyl chloride is used as the thermoplastic resin, excellent adhesion is achieved.
[0034] The above-mentioned adhesive layer is formed by the moisture-curable polyurethane hot-melt resin composition of the present invention. As a method for forming the adhesive layer, for example, the following method can be cited: after the above-mentioned moisture-curable polyurethane hot-melt resin composition is melted at 100-140°C, it is applied to the above-mentioned thermoplastic resin layer or the above-mentioned substrate using a coating machine method such as a roller coater, a spray coater, a T-die coater, a knife coater, a comma coater, a dispenser, inkjet printing, screen printing, offset printing, etc. precision methods; nozzle coating, etc., and then laminated.
[0035] After the two layers are bonded together using the adhesive, the adhesive may be dried and cured by a known method as needed.
[0036] The synthetic leather may be provided with a surface treatment layer on the basis of the thermoplastic resin layer. For example, a surface treatment layer formed of a known solvent-based urethane resin, water-based urethane resin, solvent-based acrylic resin, water-based acrylic resin, etc. may be used as the surface treatment layer.
[0037] Example
[0038] Hereinafter, the present invention will be described in more detail using examples.
[0039] [Example 1]
[0040] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 122 parts by mass of polytetramethylene glycol (number average molecular weight: 2,000, hereinafter referred to as "PEt-1"), 73 parts by mass of polyester polyol (a substance obtained by reacting 1,6-hexanediol with phthalic acid, number average molecular weight: 2,000, hereinafter referred to as "PEs-1"), and 49 parts by mass of polyester polyol (a substance obtained by reacting 1,6-hexanediol with sebacic acid, number average molecular weight: 3,500, hereinafter referred to as "PEs-2") were added and mixed, and heated under reduced pressure at 100° C. to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 57 parts by mass of 4,4'-diphenylmethane diisocyanate (hereinafter referred to as "MDI") melted at 70°C was added, and the mixture was reacted at 110°C for about 3 hours under a nitrogen atmosphere until the isocyanate group content became constant, thereby obtaining a hot-melt urethane prepolymer. 0.45 parts by mass of methanesulfonic acid (hereinafter referred to as "compound (B1)") was added to 100 parts by mass of the hot-melt urethane prepolymer to obtain a moisture-curable polyurethane hot-melt resin composition (1).
[0041] [Example 2]
[0042] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 119 parts by mass of PEt-1, 50 parts by mass of PEs-1 and 30 parts by mass of PEs-2 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 44 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content reached a constant, thereby obtaining a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 0.1 parts by mass of the compound (B1) was added to obtain a moisture-curable polyurethane hot-melt resin composition (2).
[0043] [Example 3]
[0044] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 188 parts by mass of polypropylene glycol (number average molecular weight: 2,000, hereinafter referred to as "PEt-2"), 68 parts by mass of PEs-1, and 85 parts by mass of polyester polyol (a substance obtained by reacting ethylene glycol, neopentyl glycol, 1,6-hexanediol and adipic acid, number average molecular weight: 5,500, hereinafter referred to as "PEs-3") were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 69 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C for about 3 hours in a nitrogen atmosphere until the isocyanate group content became constant, thereby obtaining a hot-melt urethane prepolymer. 0.3 parts by mass of the compound (B1) was added to 100 parts by mass of the hot-melt urethane prepolymer to obtain a moisture-curable polyurethane hot-melt resin composition (3).
[0045] [Example 4]
[0046] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 52 parts by mass of PEt-1, 22 parts by mass of PEs-1 and 13 parts by mass of PEs-2 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 19 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content reached a constant, thereby obtaining a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 0.25 parts by mass of the compound (B1) was added to obtain a moisture-curable polyurethane hot-melt resin composition (4).
[0047] [Example 5]
[0048] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 83 parts by mass of PEt-2, 19 parts by mass of PEs-1 and 26 parts by mass of PEs-3 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 28 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content reached a constant, thereby obtaining a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 0.85 parts by mass of the compound (B1) was added to obtain a moisture-curable polyurethane hot-melt resin composition (5).
[0049] [Example 6]
[0050] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 208 parts by mass of PEt-1, 48 parts by mass of PEs-1 and 64 parts by mass of PEs-3 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 66 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content reached a constant, thereby obtaining a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 0.3 parts by mass of the compound (B1) was added to obtain a moisture-curable polyurethane hot-melt resin composition (6).
[0051] [Example 7]
[0052] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 29 parts by mass of PEt-1, 29 parts by mass of PEt-2, 19 parts by mass of PEs-1 and 19 parts by mass of PEs-2 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 21 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content became constant, thereby obtaining a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 0.1 parts by mass of the compound (B1) was added to obtain a moisture-curable polyurethane hot-melt resin composition (7).
[0053] [Example 8]
[0054] A moisture-curable polyurethane hot-melt resin composition (8) was obtained in the same manner as in Example 1 except that the type of PEt-1 was changed to biomass polytetramethylene glycol (“Bio PTMG” manufactured by Mitsubishi Chemical Co., Ltd., number average molecular weight: 2,000).
[0055] [Comparative Example 1]
[0056] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 67 parts by mass of PEt-1, 24 parts by mass of PEs-1 and 18 parts by mass of PEs-2 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 24 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content reached a constant, thereby obtaining a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 0.005 parts by mass of the compound (B1) was added to obtain a moisture-curable polyurethane hot-melt resin composition (R1).
[0057] [Comparative Example 2]
[0058] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 139 parts by mass of PEt-2, 58 parts by mass of PEs-1 and 35 parts by mass of PEs-2 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 52 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content reached a constant to obtain a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 2 parts by mass of compound (B1) were added to obtain a moisture-curable polyurethane hot-melt resin composition (R2).
[0059] [Comparative Example 3]
[0060] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 58 parts by mass of PEt-1, 58 parts by mass of PEs-1 and 50 parts by mass of PEs-3 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 32 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content became constant, thereby obtaining a hot-melt urethane prepolymer, and a moisture-curable polyurethane hot-melt resin composition (R3) was obtained.
[0061] [Comparative Example 4]
[0062] In a four-necked flask equipped with a thermometer, a stirrer, an inert gas inlet and a reflux condenser, 54 parts by mass of PEt-1, 81 parts by mass of PEs-1 and 45 parts by mass of PEs-3 were added, mixed, and heated under reduced pressure at 100°C to dehydrate until the water content in the flask became 0.05% by mass or less. Next, the flask was cooled to 90°C, 37 parts by mass of MDI melted at 70°C was added, and the mixture was reacted at 110°C under a nitrogen atmosphere for about 3 hours until the isocyanate group content reached a constant, thereby obtaining a hot-melt urethane prepolymer. With respect to 100 parts by mass of the hot-melt urethane prepolymer, 0.3 parts by mass of the compound (B1) was added to obtain a moisture-curable polyurethane hot-melt resin composition (R4).
[0063] [Method for determining number average molecular weight and weight average molecular weight]
[0064] The number average molecular weight of the polyol used in Examples and Comparative Examples refers to a value measured by gel permeation column chromatography (GPC) under the following conditions.
[0065] Measuring device: High-speed GPC device (Tosoh Corporation "HLC-8220GPC")
[0066] Column: The following columns manufactured by Tosoh Corporation were connected in series and used.
[0067] "TSKgel G5000" (7.8mm I.D. × 30cm) × 1 piece
[0068] "TSKgel G4000" (7.8mm I.D. × 30cm) × 1 piece
[0069] "TSKgel G3000" (7.8mm I.D. × 30cm) × 1 piece
[0070] "TSKgel G2000" (7.8mm I.D. × 30cm) × 1 piece
[0071] Detector: RI (differential refractometer)
[0072] Column temperature: 40°C
[0073] Eluent: Tetrahydrofuran (THF)
[0074] Flow rate: 1.0mL / min
[0075] Injection volume: 100 μL (tetrahydrofuran solution with a sample concentration of 0.4 mass %)
[0076] Standard samples: The following standard polystyrene was used to prepare a calibration curve.
[0077] (Standard Polystyrene)
[0078] "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation
[0079] "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation
[0080] "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation
[0081] "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation
[0082] "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation
[0083] "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation
[0084] "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation
[0085] "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation
[0086] "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation
[0087] "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation
[0088] "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation
[0089] "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation
[0090] "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation
[0091] "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation
[0092] [How synthetic leather is made]
[0093] In a constant temperature and humidity chamber adjusted to 23°C and 50±5%, a gravure coater was used to coat a polyvinyl chloride sheet at a temperature of 40±5 g / m 2 The moisture-curable polyurethane hot-melt resin composition obtained in the examples and comparative examples was intermittently coated in a manner and laminated with a polyester fabric, and the resultant was cured for 24 hours at a temperature of 23° C. and a humidity of 50±5%, thereby obtaining a synthetic leather.
[0094] [Evaluation method of adhesiveness]
[0095] The peel strength of each synthetic leather obtained was measured using Tensilon (Tensilon universal testing machine “RTC-1210A” manufactured by ORIENTEC Corporation) at a crosshead measurement speed of 200 mm / min. 6 N / cm or more was evaluated as “○”, and less than 6 N / cm was evaluated as “×”.
[0096] [Evaluation method of low temperature flexural properties]
[0097] Each of the obtained synthetic leathers was subjected to a bending test using a deflectometer (-10°C, 100 times / minute) to measure the number of times until cracks occurred on the surface of the synthetic leather. 20,000 times or more was evaluated as "○", and less than 20,000 times was evaluated as "×".
[0098] [Durability evaluation method]
[0099] The moisture-curable polyurethane hot-melt resin composition obtained in the embodiment and the comparative example was applied with a roll coater in a thickness of 30 microns, and then cured for more than 24 hours under the conditions of temperature 23°C and humidity 50±5%, to prepare a film. Next, the obtained film was cut into strips with a width of 5 mm and a length of 50 mm, and the tensile tester "Autograph AG-i" (manufactured by Shimadzu Corporation) was used to stretch the test piece at a temperature of 23°C and a crosshead speed of 10 mm / second, and the 100% modulus (MPa) of the test piece was measured. The distance between the chucks at this time was set to 40 mm. In addition, for the durability test, the prepared film was left to stand for 5 weeks under the conditions of temperature 70°C and humidity 95±5%, and the strength of the film after standing was measured. The value of the 100% modulus (MPa) at this time was measured, and the value was divided by the value of the 100% modulus (MPa) of the test piece before the durability test, and the resulting value was used as the retention rate of the 100% modulus. A retention rate of 30% or more was designated as “○”, a retention rate of 10% or more and less than 30% was designated as “△”, and a retention rate of less than 10% was designated as “×”.
[0100] [Table 1]
[0101]
[0102] [Table 2]
[0103]
[0104] [Table 3]
[0105]
[0106] It is found that Examples 1 to 8, which are moisture-curable polyurethane hot-melt resin compositions of the present invention, are excellent in adhesiveness, low-temperature flexural properties, and durability.
[0107] On the other hand, in Comparative Example 1, the content of the compound (B) was below the range specified in the present invention, and the adhesiveness was poor.
[0108] Comparative Example 2 is an embodiment in which the content of the compound (B) exceeds the range specified in the present invention, and the durability is poor.
[0109] Comparative Example 3 is an embodiment in which the amount of the polyether polyol (a1) used is below the range specified in the present invention and the compound (B) is not used, and the adhesiveness and low-temperature flexural properties are poor.
[0110] Comparative Example 4 is an embodiment in which the amount of the polyether polyol (a1) used is below the range specified in the present invention, and the low-temperature flexural properties are poor.
Claims
1. A moisture-curable polyurethane hot-melt resin composition, characterized in that: Contains a hot-melt urethane prepolymer (A) having an isocyanate group and a compound (B) having a sulfonic acid group, The hot melt prepolymer (A) is made of a polyol (a) containing 50% by mass or more of a polyether polyol (a1). The content of the compound (B) is in the range of 0.01 to 1 part by mass based on 100 parts by mass of the hot-melt urethane prepolymer (A).
2. The moisture-curable polyurethane hot-melt resin composition according to claim 1, wherein The compound (B) is methanesulfonic acid.
3. An adhesive, characterized in that: A moisture-curable polyurethane hot-melt resin composition according to claim 1.
4. A synthetic leather, characterized in that: The adhesive layer according to claim 3 comprises at least a thermoplastic resin layer.
5. The synthetic leather according to claim 4, wherein The thermoplastic resin is polyvinyl chloride.
Citation Information
Patent Citations
Method for coating an extruded thermoplastic substrate and article formed thereby
JP2008514403A